Teacher self-disclosure as essential factor for instructional strategy and content building in ESL writing classroom / Paul GnanaSelvam Pakirnathan ... [et al.] - Pakirnathan, Paul GnanaSelvam; Suppiah, S. Maartandan; -, Daljeet Singh Sedhu; Kepol, Napisah (Universiti Teknologi MARA, 2023)
Past studies found that teacher self-disclosure positively impacted the socio-psychological aspect of teaching and learning within its dimensions of amount, relevance and negativity. However, much understanding about teacher self-disclosure today is derived from quantitative studies using established scales, conducted in non-Asian countries and usually in high school or college settings. Investigations pertaining to teacher self-disclosure in the English as a Second Language (ESL) classroom and its effects on language learning are limited. Using the qualitative approach, this exploratory study, therefore, aimed to investigate factors essential for understanding teacher selfdisclosure in the Malaysian ESL writing classroom. An ESL teacher was observed in an Academic Writing course that comprised 32 lecture and tutorial contact hours at a private institution of higher learning in Malaysia during a fourteen-week semester. A one-to-one teacher interview was then conducted to supplement the observational data. Thematic analysis was conducted to analyse data transcriptions using NVivo 12. Two main factors emerged from the analysis, revealing that the ESL writing teacher employed self-disclosures as instructional strategies and content building strategies. Teacher self-disclosure, therefore, has important implications for teachers and the teaching of writing in the ESL classroom.